A parallel scalable multigrid method and HOC scheme for anisotropy elliptic problems. (3rd April 2017) - Li, Zhao-Hui; Chen, Lei; Tao, Wen-Quan
ABSTRACT: Anisotropy problems are widely encountered in practical applications. In the present paper, a parallel and scalable multigrid (MG) method combined with the high-order compact difference scheme is employed to solve an anisotropy model equation on a rectangular domain. The present method is compared with the MG combined with the standard central difference scheme. Numerical results show that the MG method combined with the high-order compact difference scheme is more accurate and efficient than the MG with the standard central difference scheme for solving anisotropy elliptic problems. MG components (restriction, prolongation, relaxation, and cycling) and the corresponding parallelism characteristics are also discussed.